2008
DOI: 10.1097/wad.0b013e3181750a65
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Metabolic and Cognitive Changes in Mild Cognitive Impairment Patients

Abstract: Advancements in clinical therapies have identified the need for biomarkers of early Alzheimer disease that distinguish the earliest stages of pathology and target those patients who are likely to gain the most benefit. The aim of this study was to characterize the longitudinal metabolic changes measured by 1H magnetic resonance spectroscopy in correlation to neuropsychologic indices of episodic memory, attention and mental processing speed, language facility, and executive function in subjects with mild cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…NAA or NAA/Cr , especially those of the hippocampus, often correlate with memory test scores [83, 92, 97, 98] and so can be related to memory function and to predict AD with relatively high accuracy [91, 92, 98]. They also showed some localization effects, including two distinct metabolite profiles: whereas most subjects with MCI displayed a decrease in NAA , Cho , Cr , and Glx at the one-year follow-up, 36% of subjects showed an increase in NAA , which was associated with an improvement of executive function [82], suggesting a neurocompensatory response early in the course of AD. A study by Schott et al (2010), which involved six MRS evaluations over 24 months and compared clinically confirmed AD with healthy controls, reported that the baseline NAA/mI in the posterior cingulate gyrus distinguished AD from HC, with approximately 80% sensitivity and specificity [99].…”
Section: Resultsmentioning
confidence: 99%
“…NAA or NAA/Cr , especially those of the hippocampus, often correlate with memory test scores [83, 92, 97, 98] and so can be related to memory function and to predict AD with relatively high accuracy [91, 92, 98]. They also showed some localization effects, including two distinct metabolite profiles: whereas most subjects with MCI displayed a decrease in NAA , Cho , Cr , and Glx at the one-year follow-up, 36% of subjects showed an increase in NAA , which was associated with an improvement of executive function [82], suggesting a neurocompensatory response early in the course of AD. A study by Schott et al (2010), which involved six MRS evaluations over 24 months and compared clinically confirmed AD with healthy controls, reported that the baseline NAA/mI in the posterior cingulate gyrus distinguished AD from HC, with approximately 80% sensitivity and specificity [99].…”
Section: Resultsmentioning
confidence: 99%
“…There have been few MRS prospective studies reported (Kantarci et al , 2007; Olson et al , 2008; Pilatus et al , 2009; Schott et al , 2010). Metabolite levels in healthy controls acquired using similar methods as described here remain relatively unchanged over time compared to those observed in the study patient.…”
Section: Discussionmentioning
confidence: 99%
“…They found that beyond the effects of age and estimated intelligence, only NAA significantly contributed to explaining the variance in executive function. This has been supported by Kantarci et al (2002) and Olson et al [39,40]. However Valenzuela et al [30] reported an unexplained reduction in NAA/Cr measures in the hippocampus following memory training.…”
Section: Introductionmentioning
confidence: 67%